Intrinsic Brain Activity in Temporal Lobe Epilepsy With and Without Depression: Insights From EEG Microstates - Sun, Yueqian; Ren, Guoping; Ren, Jiechuan; Wang, Qun (Frontiers in Neurology, 2022)
Background: Depression is the most common psychiatric comorbidity of temporal lobe epilepsy (TLE). In recent years, studies have focused on the common pathogenesis of TLE and depression. However, few of the studies focused on the dynamic characteristics of TLE with depression. We tested the hypotheses that there exist abnormalities in microstates in TLE patients with depression. Methods: Participants were classified into TLE patients with depression (PDS, n = 19) and TLE patients without depression (nPDS, n = 19) based upon the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition. Microstate analysis was applied based on 256-channel electroencephalography to detect the dynamic changes in whole brain. The coverage (proportion of time spent in each state), frequency of occurrence and duration (average time of each state) were computed. Results: PDS patients showed a shorter mean microstate duration with higher mean occurrence per second compared to nPDS patients. There was no difference between the two groups in the coverage of microstate A-D. Conclusions: This is the first study to present the temporal fluctuations of EEG topograph in comorbid depression in TLE using EEG microstate analysis. The temporal characteristics of the four canonical EEG microstates were significantly altered in patients with TLE suffer from comorbid depression.